Effect of Terminalia Catappa Linn extract on wastewater - Mardiyah Zahidi, 1986- (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Environmental)) - Faculty Civil Engineering, Universiti Teknologi Malaysia, 2008